Impact of refugees and migrants on Visegrad Group economy - Muratova, Dilnaz; Kotrba, Vojtěch; Krejčová, Nikola, 1974-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2023)
Refugees and immigrants have various impacts on the economies of host countries, influenced by factors such as language barriers and differing skill levels that may affect the newcomers' integration process. Successful integration is crucial for overall development and positive economic outcomes. The subject of migration has consistently been relevant throughout history, with relevance today due to the ongoing war in Ukraine. The limited existing studies on this topic enhance the value of my thesis. The Visegrad Group (V4) countries, having received a substantial number of refugees from Ukraine, serve as a pertinent focus for this study. The research aimed to analyze the effects of Ukrainian immigrants and refugees on the development and income inequality of V4 countries in Europe. In this study, I investigated the impact of Ukrainian refugees on income inequality using both Fixed Effect and Random Effect regression models during the timeframe of 2022–2023. To assess the influence of Ukrainian immigrants on GDP per capita, a Fixed Effect model spanning from 2012 to 2023 was employed. Furthermore, the study evaluated the effects of Ukrainian immigrants on income inequality from 2012 to 2022, utilizing Fixed Effect, Random Effect, and 2SLS methods. Accordingly, the refugee rate increases the income inequality, the immigrants don’t have statistically significant results, while the direct effect of Ukrainian immigrants on GDP per capita is negative impact of them through labour force is positive.
Vedoucí práce: Vojtěch Kotrba
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses